“El juego como una opción para la evangelización en la propuesta asociacionista de la Unidad Educativa Técnico Salesiano de la ciudad de Cuenca” - Curay Correa, Luis Vicente (2015)
The development of the present thesis project has as a basic intention to give a proposal in which the inestimable value of the game and the evangelizing task be put together. As a Church, all of us are called to do that and the students from “Unidad Educativa Técnico Salesiano” from Cuenca are also invited to participate in the banquet of the Gospel, to live the experience of Jesus in all educational environments, and in this case, in the Salesian associations (clubs). For the achievement of this goal, we have developed a theoretical framework to build and support the code of faith of the scientific and academic Church's Magisterium to defend the importance of this study through proper and verifiable arguments. After that, the implementation of a survey will allow us to collect data which are related to two items: what the student thinks about the game in harmony with education, and the perception of the clubs’ tutors in regard to the importance of evangelization in their educational labor, the eases and difficulties encountered from different perspectives, and what they need to introduce the evangelization of their youth through the game. Finally, the third chapter integrates the data obtained and their respective interpretation, always relying on the theoretical framework presented to develop an evangelization proposal applicable to all the different clubs in the four areas that are present: apostolic, sports, cultural and scientific.